Metformin as a cellular protector; a synoptic view of modern evidences - Wiernsperger Nicolas (Society of Diabetic Nephropathy Prevention, 2015)
Due to limited knowledge and chemical class effect assimilation the biguanide metformin has long been considered as a useful but risky treatment for type 2 diabetes treatment. The worldwide long-term experience of clinical use of this compound and the growing knowledge about its mechanisms of action have, however, reversed this reputation to the point that nowadays it is not only considered as relatively harmless but even increasingly as a cellular protector. The present mini-review simply aims at giving a brief overview of the evidences accumulated overt recent periods and to provide the reader with information as to mechanistic hypotheses, knowing that there remains a lot to be done to better understand the pleiotropic behavior of this drug and its possible future new therapeutic applications. Data are shown at a glance for the kidney but also for other various organs and cell types corroborating this new notion for an old drug and paradox.